Geocomputation a practical primer - Brunsdon, Chris; Singleton, Alex (London SAGE, 2015)
The only student focused, applied primer for Geocomputation in the social sciences. With example code and data sets provided as add-ons, it enables readers to work through all the examples themselves. An accessible text, specifically designed for readers who are new to Geocomputation as an area of research.
Introduction -- Describing how the world looks Spatial Data Visualisation with R / James Cheshire and Robin Lovelace - Geographical Agents in Three Dimensions / Paul Torrens - Scale, Power Laws, and Rank Size in Spatial Analysis / Michael Batty -- Exploring movements in space Agent-Based Modeling and Geographical Information Systems - Andrew Crooks - Microsimulation Modelling for Social Scientists / Kirk Harland and Mark Birkin - Spatio-Temporal Knowledge Discovery / Harvey J. Miller - Circular Statistics / David Rohde and Jonathan Corcoran -- Making geographical decisions Geodemographic Analysis / Alexandros Alexiou and Alexander Singleton - Social Area Analysis and Self Organizing Maps / Seth Spielman and David Folch - Kernel density estimation and Percent Volume Contours / Daniel Lewis - Location-Allocation Models / Melanie Tomintz, Graham Clarke and Nawaf Alfadhli -- Explaining how the world works Geographically Weighted Generalised Linear Modelling / Tomoki Nakaya - Spatial Interaction Models / Karyn Morrissey - Python Spatial Analysis Library (PySAL) : An Update And Illustration / Sergio Rey - Reproducible Research : Concepts, Techniques and Issues - Chris Brunsdon and Alex Singleton -- Enabling interactions Using Crowd-Sourced Information to Analyse Changes in the Onset of the North American Spring / Chris Brunsdon and Lex Comber - Open Source GIS software / Oliver O'Brien - Public Participation in Geocomputation to Support Spatial Decision Making / Richard Kingston -- Conclusion -- References
Keywords: Geographic information systems; Information storage and retrieval systems -- Geography